Description of Students Mathematical Understanding Ability Obtained by Problem Based Learning (PBL) and Inquiry Based Learning (IBL) Models - Supriatna, Irfan; Wahyudin; Turmudi (International Conference on Elementary Education, 2024)
This research aims to obtain a comprehensive picture of students' acquisition of Mathematical Understanding Ability using the PBL and IBL models. The method in this research is a mixed method The sample in this research was 16 students in class IV at SDN 1 Girimukti and 12 students in class IV at SDN 2 Girimukti. The results of the research based on SPSS calculations show that descriptively the average gain in mathematical understanding ability of students who studied with PBL was 77.81, higher than the average gain in mathematical understanding ability of students who studied with IBL which was 63.33. Distribution of scores for the acquisition of mathematical understanding ability of students who learning with PBL is more spread out compared to the scores for gaining mathematical understanding abilities of students who study with IBL, as can be seen from the standard deviation scores in both classes, where the PBL class is 8.2 and the IBL is 7.8. The conclusion shows that the description of the mathematical understanding abilities of students who obtain the PBL model is higher than the mathematical understanding abilities of students with the IBL model seen from the mean and standard deviation.